Metformin prevents oxidative stress and apoptosis of ovarian granulosa cells in polycystic ovary syndrome via activation of Nrf2-HO-1 pathway - Jin-Jing Li; Hong-Lian Wu; Yang Lv; Ye-Min Qin; Xi-Xi Qiu; Xi-Xi Cai (Gynecological Endocrinology)
Objective The purpose of the study is to investigate therapeutic effects of metformin on improving PCOS and the underlying mechanism.Methods PCOS modeling and metformin treatment in rats was performed by subcutaneous injection of dehydroepiandrosterone (DHEA) daily, high-fat diet feeding, and intragastric administration of metformin for 21 consecutive days. PCOS modeling and metformin treatment in KGN cells was performed by DHEA treatment at a concentration of 10−5 mol/l for 48 h and metformin treatment (10−7 M) for 24 h.Results After PCOS modeling, rats showed more weight gain, improved glucose tolerance, disrupted estrous cycles, characteristic polycystic ovary morphology, more apoptotic cells in the ovary with enhanced oxidative stress, and declined Nrf2 and HO-1 expressions. Metformin treatment effectively alleviated characteristic polycystic ovary morphology, prevented apoptosis and oxidative stress, and decreased Nrf2 and HO-1 expressions of PCOS rats. Similarly, metformin treatment reduced the apoptosis and oxidative stress in DHEA-treated KGN cells, but anti-apoptotic and antioxidant effects of metformin were partially reversed by Nrf2 knockdown in DHEA-treated KGN cells.Conclusion The findings of the study suggest that metformin protects ovarian granulosa cells against oxidative stress and apoptosis in the context of PCOS via activation of Nrf2-HO-1 pathway.